Service Delivery with More Districts in Uganda : Fiscal Challenges and Opportunities for Reforms - World Bank (Washington, DC, 2013)
Ugandan decentralization efforts of the 1990s represented an unusually authentic and powerful local government reform, compared to similar efforts pursued in many other low-income countries. However, over time the changing interests of the central agencies, dissatisfaction with service outcomes, and the overall dynamics of the country's governance resulted in the adoption of a number of re-centralizing policies. The objective of this report is to take stock of the fiscal and institutional arrangements for service delivery by local governments in the context of district proliferation and in view of recent trends in national public finance, as well as to identify policy options that could facilitate improved service delivery. The report finds that, while district proliferation has not had any major effect on public finances so far, it may have serious adverse effects in the future if the institutional structures and funding mechanisms of district governments are not adjusted to the new realities. Its effect on public expenditure has been rather small since an increasing number of positions in district governments remain vacant, and because a recent bout of inflation has eroded their wage bills. Furthermore, at present the average population of a district is roughly equivalent to that of similar jurisdictions in other countries. The report concludes with a number of institutional and fiscal proposals designed to reduce this risk and to improve value-for-money in service delivery more generally. If Uganda manages to use district proliferation as an opportunity to implement these changes, the resulting fiscal savings and improvements in value-for-money would make it much easier to cover the costs of that process.